How Leadership and Work Discipline Affect Employee Performance: Organizational Commitment as a Mediating - Nainin Nahdiyah Izzah Dinillah; Setiani, Setiani (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This study aims to strengthen the theories of several researchers and analyze the effect of leadership and work discipline on employee performance with organizational commitment as mediation. This research is explanatory research with a quantitative approach. The population and sample were 165 employees at PT G4S Indonesia Plant Sukorejo. The sampling technique is saturated sampling. The data analysis technique uses path analysis with partial least squares (PLS) through validity, reliability, and hypothesis testing. The results showed that there was no influence between leadership and employee performance. Work discipline affects employee performance. Organizational commitment affects employee performance. Organizational commitment is unable to mediate the relationship between leadership and employee performance. At the same time, organizational commitment can mediate the relationship between work discipline and employee performance. The research implications are expected to help in the development of human resource management theory by providing empirical evidence of how these variables interact with each other. Findings regarding the mediating role of organizational commitment can strengthen or modify existing theories regarding employee performance. The contribution of this research is that PT G4S Indonesia Plant Sukorejo can use the results of this study to develop more effective managerial strategies to improve employee performance through improving leadership and work discipline.